The Teller's Tale : Lives of the Classic Fairy Tale Writers - Raynard, Sophie (Book collections on Project MUSE., 2012)
"Intriguing, updated portraits of classic fairy tale authors. This book offers new, often unexpected, but always intriguing portraits of the writers of classic fairy tales. For years these authors, who wrote from the sixteenth to the nineteenth centuries, have been either little known or known through skewed, frequently sentimentalized biographical information. Jacob and Wilhelm Grimm were cast as exemplars of national virtues; Hans Christian Andersen's life became - with his participation - a fairy tale in itself. Jeanne-Marie Leprince de Beaumont, the prim governess who wrote moral tales for girls, had a more colorful past than her readers would have imagined, and few people knew that nineteen-year-old Marie-Catherine d'Aulnoy conspired to kill her much-older husband. Important figures about whom little is known, such as Giovan Francesco Straparola and Giambattista Basile, are rendered more completely than ever before. Uncovering what was obscured for years and with newly discovered evidence, contributors to this fascinating and much-needed volume provide a historical context for Europe's fairy tales."--Project Muse